Comparative Effectiveness of Two Light Curing Units on the Properties of Dental Resin Composites - Afreen Bilgram; Fazal-; Malik SaleemShaukat; Aeeza Malik; Talha Nayab; Wasif Iqbal (ziauddin University, 2024)
Background: Setting of conventional glass ionomers cement and dental resin composites as ﬁlling materials is predominantly through polymerization reaction, which is usually induced by light. The objective of this study was to assess the temperature changes, light intensities, sorption and solubility capability and comparative micro hardness in Dental Resin Composites (DRC) by using two different light curing units that is Quartz Tungsten Halogen (QTH) and Light Emitting Diodes (LED). Methods: This analytical, experimental, in-vitro study was spanned over one month, conducted in the laboratory of Dental Materials, Dr. Ishrat-ul-Ibad Khan Institute of Oral Health Sciences. Through non-probability, convenient sampling, 60 samples of DRCs was prepared as 10mm in diameter and 2mm in thickness in the steel moulds by a single trained operator. Effect of heat generation, light intensities, sorption and solubility and micro hardness during polymerization of DRCs were all measured. Statistical analysis was done using SPSS with descriptive statistics and two sample independent t-tests. The p-value of <0.05 was considered signiﬁcant at 95 % conﬁdence level. Results: Mean surface micro hardness of DRC was found to be 15.48±0.46 and 18.26±0.53 when QTH and LED lamps were employed respectively. Whereas, mean light intensity of QTH and LED lamps were found to be 434 and 925mW/cm2. No signiﬁcant difference in temperature change during polymerization reaction (p=0.128) and in sorption and solubility capability (p=0.001) of DRC was observed. Conclusion: Light-emitting diodes were evaluated to be more effective than Quartz Tungsten Halogen Light in achieving increased surface micro hardness of DRC. Keywords: Light; Glass Ionomer Cements; Tungsten; Hardness.